'Wagon-wheel' mask as a tool to study anisotropy of porous silicon formation rate - Astrova, Ekaterina V (Springer, 2012)
Relationship between the rate of electrochemical formation of mesoporous Si and the crystallographic directions has been studied by local anodization of wafers through a mask having the form of narrow long wedges radiating from the center in all directions (‘wagon-wheel’ mask). The etching rates were found from the side etching under the thin transparent n-Si mask. On p(+)-substrates of various orientation diagrams characterizing the distribution of pore formation rates over different directions in the wafer plane were constructed for the first time. The wagon-wheel method was applied to study the current dependence of the anisotropy. It was found that the orientation-related difference between the pore formation rates is 5% to 25%, depending on the crystallographic direction and the etching current density. At a current density of approximately 9 mA/cm(2), the etching rates are related as V100:V113:V110:V112:V111 = 1.000:0.900:0.836:0.824:0.750. A general tendency is observed toward weakening of the anisotropy with increasing current. The highest rate always corresponds to the <100 > direction, and the rate ratio between the other directions varies with increasing current, which leads to a change of their sequence.